The Effect of Maternal Body Mass Index on in Vitro Fertilization-Intracytoplasmic Sperm Injection Treatment: A Prospective Comparative Study - Zeynep Ozturk Inal; Hasan Ali Inal (Gynecology Obstetrics & Reproductive Medicine)
Objective: To evaluate whether or not maternal body mass index affects pregnancy rates following in vitro fertilization-intracytoplasmic sperm injection treatment.